Hepatoprotective and antioxidant effect of Carissa spinarum root extract against CCl4 and paracetamol-induced hepatic damage in rats - Karunakar Hegde, Arun B. Joshi (Bangladesh Pharmacological Society, 2010)
Ethanolic extract of the roots of C. spinarum was evaluated for hepato-protective and antioxidant activities in rats. Oral pre-treatment with ethanolic extract (100, 200 and 400 mg/kg) showed significant hepatoprotective activity against CCl4 and paracetamol-induced hepatotoxicity by decreasing the activities of bilirubin and lipid peroxidation, and significant increase in the levels of uric acid, glutathione, super oxide dismutase, catalase and protein in a dose dependent manner, which was confirmed by the decrease in liver wet weight and histopathological examination. The extract possessed strong antioxidant activity. This suggests that the hepatoprotective activity of C. spinarum is possibly attributed to its free radical scavenging properties.